Reimagining Kantian Ethics: Expanding Moral Consideration to Non-Rational Nature and Animal in Environmental Ethics - UDISI , Ebikisei Stanley (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
This paper critically examines the capacity of Immanuel Kant’s ethical framework to incorporate moral concern for non-rational nature, with a particular focus on non-rational animals. Through an analysis of four contemporary Kantian scholars—Lara Denis, Onora O’Neill, Allen Wood, and Christine Korsgaard—the study explores how Kantian ethics might be reinterpreted to address the moral status of non-rational beings. The analysis is structured into two main sections. The first investigates Denis and O’Neill’s indirect duty approach, which grounds human obligations to animals in the pursuit of moral self-perfection. While their revisions offer a pathway for moral consideration of animals, I argue that their accounts struggle to reconcile Kant’s rigid distinction between rational humans and non-rational animals, risking the dilution of core Kantian principles. The second section evaluates Wood and Korsgaard’s more radical proposals, which advocate for direct moral duties toward non-rational nature. Wood posits that animals possess traces of rationality, warranting respect, while Korsgaard grounds obligations in the natural goods of animals, emphasizing their capacity to experience what is naturally good or bad. However, I contend that both approaches risk departing from Kant’s insistence on rationality as the sole foundation for intrinsic moral worth. Among the four perspectives, O’Neill’s indirect duty approach emerges as the most promising, as it remains closest to Kant’s original framework. Nevertheless, I highlight its limitations, particularly its lack of precision in explaining how concern for non-rational animals contributes to moral self-perfection. Building on O’Neill’s insights, I propose an extension of Kant’s Kingdom of Ends formula, which recognizes the natural goods of non-rational beings without attributing moral agency to them. This framework establishes human obligations to promote the well-being of non-rational nature while preserving Kant’s emphasis on rationality as the basis for moral valuation. This paper underscores the challenges of integrating non-rational beings into Kant’s ethical system while offering a refined approach that balances Kantian principles with contemporary moral concerns.